2021
DOI: 10.1097/pts.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Missed Nursing Care in a Sample of High-Dependency Italian Nursing Home Residents: Description of Nursing Care in Action

Abstract: The aim of the study was to describe omitted or delayed nursing care (i.e., missed nursing care [MNC]) in a sample of Italian nursing homes (NHs).Methods: Nurses from 50 NHs located in Northern Italy selected the 20 most dependent residents in their care and reported instances of MNC for three to five consecutive shifts. They described the type of MNC, its cause(s), management, recurrence, and severity of possible consequences for the resident. Information on the residents and the NH was also collected. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Perhaps, the need for multitasking forces nurses to select implicitly those areas of nursing care that prevent harm due to the quality of care and patient safety. Once again, these findings confirm that nurses cannot finish all of the planned nursing care and highlight the adverse effects this phenomenon can have on the quality of health care and treatment outcomes 32…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Perhaps, the need for multitasking forces nurses to select implicitly those areas of nursing care that prevent harm due to the quality of care and patient safety. Once again, these findings confirm that nurses cannot finish all of the planned nursing care and highlight the adverse effects this phenomenon can have on the quality of health care and treatment outcomes 32…”
Section: Discussionsupporting
confidence: 53%
“…Once again, these findings confirm that nurses cannot finish all of the planned nursing care and highlight the adverse effects this phenomenon can have on the quality of health care and treatment outcomes. 32 The present study showed that only the sociodemographic factor of education affected the level of care rationing. Nurses with a vocational school education rationed nursing activities significantly less than nurses with a bachelorʼs degree.…”
Section: Discussionmentioning
confidence: 48%
“…This study reveals that nurses most frequently ration the activities related to the first and second stage of the caring process (diagnosing the bio-psycho-social condition of the patient and planning activities aimed at solving the problems of patients), which finally translates into lower quality of provided care and worse treatment outcomes for patients (Campagna et al, 2020 ). In contrast, the positive aspect is that, as has been demonstrated, the least frequently rationed activities include applying necessary disinfection measures and preparation of patients for planned tests or therapies, which is also confirmed by other authors (Schubert et al, 2013 ; Uchmanowicz et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive data on missed nursing care are presented in the parent study. 21 Individual factors, including RNs' gender, age, work experience (in their role and in the nursing home), and educational background were assessed. Work-related factors, ie, working shift (day shift vs alternate day and night shift), employment status (agency staff, public/private sector employment, freelancer), and weekly working hours were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…Only one study investigated the severity of missed nursing care in nursing homes, as reported by a sample of RNs; results showed that RNs classified about 25% of missed nursing care as severe due to the clinical consequences and the discomfort caused to residents. 21 Missed nursing care has been associated with individual, work-related, organisational, and work environment factors; however, studies on the factors related to missed nursing care in nursing homes are lacking. In a sample of nurse aides, Knopp-Sihota et al found an association between missed nursing care and individual factors (younger age and low level of experience), work-related factors (working on the day shift), organisational factors (low number of beds and public ownership of nursing homes in rural areas), and poor work environment in terms of leadership, culture, staffing, and time for care.…”
Section: Introductionmentioning
confidence: 99%